"Righting" Conventional Wisdom: Women and Right Parties in Established Democracies. Issue 1 (10th April 2018) - O'Brien, Diana Z.
Abstract : Parties are the key actors shaping women's representation in advanced parliamentary democracies. Based on traditional patterns of feminist organizing, conventional wisdom suggests that parties of the left are the strongest advocates for women. Despite the prevalence of this claim, a burgeoning body of work indicates that parties on the right can—and often do—seek to represent women. To address these competing narratives, this article offers the first large- N, party-level study of women's descriptive and substantive representation over place and time. The results suggest that party ideology continues to affect women's representation: right parties lag behind their left counterparts with respect to women's presence in elected office, and right and left parties address women differently on their platforms. At the same time, there is significant heterogeneity among right parties. Christian democrats, for example, are more likely than conservatives to adopt voluntary gender quotas and make policy claims on behalf of women. The traditional left-right distinction is thus too coarse to fully explain party behavior in these states.